2013
DOI: 10.3762/bjoc.9.217
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical control of the photodimerization of aromatic compounds by γ-cyclodextrin thioethers in aqueous solution

Abstract: SummaryThe formation of soluble 1:2 complexes within hydrophilic γ-cyclodextrin (γ-CD) thioethers allows to perform photodimerizations of aromatic guests under controlled, homogenous reaction conditions. The quantum yields for unsubstituted anthracene, acenaphthylene, and coumarin complexed in these γ-CD thioethers were found to be up to 10 times higher than in the non-complexed state. The configuration of the photoproduct reflected the configuration of the dimeric inclusion complex of the guest. Anti-parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Hill plot gave a Hill constant of 1.8 that ascertained a positive allosteric effect in the catalytic process. PCA of coumarins within g-CD [39] in solution phase, and within b-CD in solid state [53,66] have been reported earlier. The catalytic cycle features a sequential formation of 1 : 1 host-guest complex with a binding constant (K a1 ) of 1.3 3 10 4 M À1 followed by the formation of 1 : 2 hostguest complex (K a2 : 23 10 6 M À1 ).…”
Section: Supramolecular Photocatalysis: Photocycloaddition Of Coumarinssupporting
confidence: 57%
See 1 more Smart Citation
“…Hill plot gave a Hill constant of 1.8 that ascertained a positive allosteric effect in the catalytic process. PCA of coumarins within g-CD [39] in solution phase, and within b-CD in solid state [53,66] have been reported earlier. The catalytic cycle features a sequential formation of 1 : 1 host-guest complex with a binding constant (K a1 ) of 1.3 3 10 4 M À1 followed by the formation of 1 : 2 hostguest complex (K a2 : 23 10 6 M À1 ).…”
Section: Supramolecular Photocatalysis: Photocycloaddition Of Coumarinssupporting
confidence: 57%
“…Value of such hosts in basic science has been recognized by the award of two Nobel Prizes, one in 1987 [29] and the other in 2016. [39][40][41] Among these reactions, the bimolecular PCA [2 + 2] [42] is of special significance for three reasons: (a) The product of the reaction, cyclobuatne skeleton is found in a number of natural products of potential medicinal value, [43,44] (b) PCA is the basic reaction for photopolymerization, and (c) stereo-and regio-selectivity of PCA performed within confined structures has served as indicator of the prereaction orientation, which has been useful in understanding intermolecular interactions. Recognizing the value of light-initiated reactions in the construction of natural and unnatural products we have explored the use of these cavitands as reaction containers for performing selective photochemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Wenz and co-workers reported the use of cyclodextrins for controlling the photodimerization of (E)-4′,4′-bis-(dimethylaminomethyl)stilbene E-106g (Scheme 63). 432,433 In the presence of γ-CD, exclusive formation of [2 + 2] cycloadduct anti dimer 109g was observed as a major product with minor amounts of the isomerization product Z-106g and cyclized phenanthrene product 110g. When a smaller cavity was employed (α-CD or β-CD) no dimerization was observed.…”
Section: Cyclodextrins (Cds)mentioning
confidence: 99%
“…S5-S8. † Previously, it has been reported that a γ-CD encapsulates two coumarins simultaneously to form 1 : 2 inclusion complexes and can lead to photo-dimerization in solution 45 and solid phase. 46 Zhang et al (2013) reported that, according to a Job plot, the binding stoichiometry between γ-CD and cationic viologen-connected coumarin moieties was 1 : 2.…”
Section: Resultsmentioning
confidence: 99%